Understanding Firm Dynamics with Daily Data - Lukas Hack; Davud Rostam-Afschar (Institute of Labor Economics (IZA), 2025)
How do firms' plans and expectations respond to macroeconomic shocks? We run a daily survey of German firms over the past three years. We randomize daily invitations, delivering a stable composition of firms. This allows constructing daily time series and estimating dynamic aggregate causal effects. These estimates capture firms' responsiveness conditional on the recent economic environment, making them informative for policymakers. We examine oil supply, monetary policy, and forward guidance shocks, finding that firms' plans, especially price-setting plans, respond within days to oil supply and monetary policy shocks but not to forward guidance. Finally, we investigate firm heterogeneity and expectations.
Keywords: E31; E43; E52; E58; C83; 330; oil supply; monetary policy; firms; daily data; inflation surge